Penerapan Lesson Study melalui Project Based Learning (PjBL) Pada Mata Pelajaran IPA SMP - Huda, Muhammad Khomarul; Sinaga, Yuliana K. B.; Saragih, Sarlina (Mahesa Research Center, 2024)
This article discusses the implementation and application of